1994
DOI: 10.1159/000196305
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Pulmonary Involvement in 2 Children with Niemann-Pick Disease Type B

Abstract: We present 2 cases of children with Niemann-Pick disease type B, and surprisingly with reticular lung infiltrations, although otherwise healthy in terms of pulmonary manifestation. Finding such reticular infiltrations should lead one to think of the possibility of metabolic storage disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 3 publications
1
18
0
Order By: Relevance
“…The typical chest radiograph has interstitial infiltrates with reticulonodular changes and areas of ground glass density, often out of proportion to clinical manifestations. 13 Studies in ASM knockout mice, which have histopathologic and clinical changes similar to human NPD-B patients, 14 reveal that inflammation, abnormal surfactant catabolism, and abnormal surfactant composition all contribute to lung abnormalities. 15 However, more detailed studies of lung function are required to understand better the pathophysiology of the pulmonary disease in NPD-B.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The typical chest radiograph has interstitial infiltrates with reticulonodular changes and areas of ground glass density, often out of proportion to clinical manifestations. 13 Studies in ASM knockout mice, which have histopathologic and clinical changes similar to human NPD-B patients, 14 reveal that inflammation, abnormal surfactant catabolism, and abnormal surfactant composition all contribute to lung abnormalities. 15 However, more detailed studies of lung function are required to understand better the pathophysiology of the pulmonary disease in NPD-B.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who were Ͼ18 years old and did not have pulmonary signs were given a score of 1, those with cyanosis or clubbing were given a score of 2, and those with oxygen dependence were given a score of 3. The sum of the scores from each category was the overall phenotypic severity score, which was categorized as mild (overall score 6 -11), moderate (overall score [12][13][14] or severe (overall score Ͼ15).…”
Section: Determination Of Phenotypic Severity Score and Genotype/phenmentioning
confidence: 99%
“…8 Chest radiographs in affected patients reveal interstitial infiltrates with reticulonodular changes and areas of ground-glass density that may be out of proportion to clinical findings. 16 Severely affected patients may exhibit cough, shortness of breath, and recurrent respiratory infections, 17 and some patients develop chronic oxygen dependence with progressive pulmonary failure. 18 The pathophysiology of the pulmonary disease is presumably related to the accumulation of sphingomyelin in the alveolar macrophages, although studies in the ASM knockout mouse also have shown that inflammation, abnormal surfactant catabolism, and abnormal surfactant composition all contribute to lung abnormalities.…”
Section: Genetics In Medicine | Volume 15 | Number 8 | August 2013mentioning
confidence: 99%
“…Respiratory function testing also can be useful in alerting patients and physicians to pulmonary involvement in later stages of the disease, but young NPD patients often present with normal lung function (Ferretti et al, 1996;Niggemann et al, 1994). Characteristics of the BALF have been sparsely documented in incidental cases, and BAL is not a routine procedure in type B NPD diagnosis.…”
Section: Dhami Et Almentioning
confidence: 99%
“…Respiratory infections and pulmonary function decline are a common cause of morbidity among type B NPD individuals (Lever and Ryder, 1983;Schuchman and Desnick, 2001), and may lead to death in severely affected patients. The lung pathology of type B NPD patients has been routinely characterized by radiography showing evidence of reticulonodular infiltrates (Bouziani et al, 1990;Ferretti et al, 1996;Gerbaux et al, 1971;Gogus et al, 1994;Niggemann et al, 1994). Histologic examination of autopsy lungs has also demonstrated the presence of "foamy cells" (large macrophages with cytoplasmic inclusions) in the alveolar spaces (reviewed in Minai et al, 2000).…”
mentioning
confidence: 99%